2016
DOI: 10.17582/journal.sja/2016/32.3.127.133
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization in 5 × 5 Diallel Crosses for Yield Traits in Bread Wheat

Abstract: The seed of five parental cultivars alongwith their 10 F 1 hybrids of wheat were sown in a randomized complete block design with four replications during 2010 at Sindh Agriculture University, Tandojam, Pakistan. Genetic analysis of yield traits from half diallel crosses was carried-out. Mean squares due to GCA and SCA were significant for days to 75% maturity, tillers plant -1 , spike length, spike density, grains spike -1 , grain yield plant -1 , seed index and harvest index. Significance of GCA and SCA varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…Highly significant differences (P≤0.01) were observed for all the studied traits except harvest index which display significant differences (P≤0.05) among wheat genotypes (table 1). Similar findings were reported by many researchers and confirmed our results [15,[16][17][18][19][20][21][22][23].…”
Section: Analysis Of Variancesupporting
confidence: 93%
See 2 more Smart Citations
“…Highly significant differences (P≤0.01) were observed for all the studied traits except harvest index which display significant differences (P≤0.05) among wheat genotypes (table 1). Similar findings were reported by many researchers and confirmed our results [15,[16][17][18][19][20][21][22][23].…”
Section: Analysis Of Variancesupporting
confidence: 93%
“…These results are in conformation with the findings of Al-Tabbal and Al-Fraihat, [28]. For grains per spike, other researchers also reported high heritability estimates [16,17]. Grain yield ha -1 exhibited high heritability (69.01%) among fourteen advanced lines and four checks (table 3).…”
Section: Heritability Estimation On Entry Mean Base Among Six Traits supporting
confidence: 88%
See 1 more Smart Citation
“…Our study showed a medium heritability (48.7%) for NKS (Table 4.4). High heritability wasalso reported for NKS by Mohammadi et al (2011) and Gerema (2021) in durum wheat and by Baloch et al (2016) in bread wheat. For PL, TKW, SDSS and GI, heritability was medium Similarly, in previous studies, it has been found that heritability for SDSS varied from moderate to high (Clarke et al, 2010, Taneva et al, 2019, Taghouti et al, 2010.…”
Section: Evaluation Of the Genotype-by-environment Interaction Throughmentioning
confidence: 70%
“…SL could be considered a key trait, as larger spikes will likely produce more grains and increase yield. Baloch et al (2016) reported highly significant variation for this trait among bread wheat varieties and high heritability. The number of kernels per spike (NKS) contributes considerably to grain yield by increasing sink strength.…”
Section: Evaluation Of the Genotype-by-environment Interaction Throughmentioning
confidence: 91%